Electrolyte for lithium-sulfur secondary battery and lithium-sulfur secondary battery comprising same

By using a specific proportion of solvent, non-solvent and lithium salt combinations in lithium-sulfur secondary batteries, the nitric acid-based and nitrite electrolytes are eliminated, and the problem of short life of lithium-sulfur batteries is solved, achieving high energy density and long life battery performance.

CN119213603APending Publication Date: 2024-12-27LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380043890.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-23
Filing Date
2023-12-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lithium-sulfur secondary batteries have short life characteristics due to polysulfide dissolution, and the existing microsolvated electrolyte system is difficult to maintain the reversible reaction of the positive/negative active material during solid phase reaction, resulting in a short battery life.

Method used

An electrolyte system is adopted that includes solvent, non-solvent and at least two types of lithium salts, wherein the lithium salt comprises LiI, the solvent and lithium salt have a specific solvent volume ratio and molar mass ratio factor value, and nitrite electrolytes are excluded, Linear ethers, cyclic ethers or mixtures thereof are used as solvents, fluorinated ethers are used as non-solvents, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide as lithium salts to inhibit polysulfide dissolution and improve battery life.

Benefits of technology

By adjusting the ratio of solvent, non-solvent and lithium salts in the electrolyte, the life characteristics and energy density of lithium-sulfur secondary batteries are improved, the dissolution of polysulfides is inhibited, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to an electrolyte for a lithium-sulfur secondary battery and a lithium-sulfur secondary battery comprising the same, and can provide a lithium-sulfur secondary battery having improved lifespan characteristics by adjusting a solvent, a non-solvent, and a lithium salt contained in the electrolyte to specific conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrolyte for a lithium-sulfur secondary battery and a lithium-sulfur secondary battery including the same.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0183762 filed in Korea on December 23, 2022, the disclosure of which is incorporated herein by reference. Background Art

[0003] Existing lithium-sulfur (Li-S) batteries using a catholyte system rely on the generation of Li 2 S X The liquid phase reaction (catholyte type) that takes place by reacting sulfur with sulfur (polysulfide intermediates) cannot make good use of the high theoretical discharge capacity of sulfur (1675 mAh / g), and the lifetime characteristics are reduced due to degradation caused by the dissolution of polysulfides. 3 Additives are used, but depletion of the additives prevents long-life performance of lithium-sulfur batteries.

[0004] Recently, a slightly solvated electrolyte (SSE) system has been proposed to suppress polysulfide dissolution, and it has been confirmed that the electrolyte without predetermined additives achieves normal operation without charging delay. However, its lifespan is still short, and thus there is a need to improve the lifespan characteristics.

[0005] In order to achieve a high energy density of 400 Wh / kg or more and 600 Wh / L or more, a lithium-sulfur secondary battery electrolyte system is required that can achieve a high energy density of 400 Wh / kg or more and 600 Wh / L or more. 2 It works and improves the life characteristics at a porosity of more than 60 volume %. Summary of the invention

[0006] Technical issues

[0007] The present disclosure is designed to solve the above-mentioned problems, and thus the present disclosure is directed to providing an electrolyte for a lithium-sulfur secondary battery having high energy density and improved life characteristics, and a lithium-sulfur secondary battery including the electrolyte.

[0008] It will be easily understood that these and other objects and advantages of the present disclosure can be achieved by the means or methods set forth in the appended claims, and combinations thereof.

[0009] Technical Solution

[0010] The inventors have found that the above-mentioned problems can be solved by an electrolyte for a lithium-sulfur secondary battery and a lithium-sulfur secondary battery including the electrolyte described below.

[0011] According to a first embodiment, the present disclosure relates to an electrolyte for a lithium-sulfur secondary battery, which includes a solvent, a non-solvent, and at least two types of lithium salts, wherein the lithium salt includes LiI,

[0012] wherein the solvent and the non-solvent have a solvent volume ratio (SVR) factor value of 0.2 to 0.7, and the SVR factor value is represented by the following formula 1, and

[0013] wherein the solvent and the lithium salt have a molar mass ratio (MR) factor value of 0.75 to 1.85, and the MR factor value is represented by the following Formula 2,

[0014] [Formula 1]

[0015] SVR factor = volume of solvent ÷ volume of non-solvent

[0016] [Formula 2]

[0017] MR factor = number of moles of solvent ÷ (number of moles of lithium salt excluding LiI).

[0018] According to a second embodiment, in the first embodiment, the present disclosure is directed to an electrolyte for a lithium-sulfur secondary battery, wherein the SVR factor value is 0.3 to 0.65.

[0019] According to a third embodiment, in the first or second embodiment, the present disclosure is directed to an electrolyte for a lithium-sulfur secondary battery, wherein the MR factor value is 1.0 to 1.75.

[0020] According to a fourth embodiment, in any one of the first to third embodiments, the present disclosure is directed to an electrolyte for a lithium-sulfur secondary battery, wherein the solvent has a solubility of 0.1M or more for the lithium salt, and the nonsolvent has a solubility of less than 0.1M for the lithium salt.

[0021] According to a fifth embodiment, in any one of the first to fourth embodiments, the present disclosure is directed to an electrolyte for a lithium-sulfur secondary battery, wherein the solvent contains a linear ether, a cyclic ether, or a mixture thereof.

[0022] According to a sixth embodiment, in any one of the first to fifth embodiments, the present disclosure is directed to an electrolyte for a lithium-sulfur secondary battery, wherein the solvent includes a mixture of a linear ether and a cyclic ether.

[0023] According to a seventh embodiment, in any one of the first to sixth embodiments, the present disclosure is directed to an electrolyte for a lithium-sulfur secondary battery, wherein the nonsolvent contains a fluorinated ether.

[0024] According to an eighth embodiment, in any one of the first to seventh embodiments, the present disclosure is directed to an electrolyte for a lithium-sulfur secondary battery, wherein the lithium salt includes lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and LiI.

[0025] According to a ninth embodiment, in any one of the first to eighth embodiments, the present disclosure is directed to an electrolyte for a lithium-sulfur secondary battery, wherein a content of the LiI is 0.1 to 3.0 parts by weight based on a total of 100 parts by weight of the electrolyte for a lithium-sulfur secondary battery.

[0026] According to a tenth embodiment, in any one of the first to ninth embodiments, the present disclosure is directed to an electrolyte for a lithium-sulfur secondary battery, wherein a content of the LiI is 0.35 to 15 parts by weight based on a total of 100 parts by weight of the lithium salt.

[0027] According to an eleventh embodiment, in any one of the first to tenth embodiments, the present disclosure is directed to an electrolyte for a lithium-sulfur secondary battery, wherein the electrolyte for a lithium-sulfur secondary battery does not include at least one of a nitric acid-based compound and a nitrous acid-based compound.

[0028] According to a twelfth embodiment, the present disclosure is directed to a lithium-sulfur secondary battery including a negative electrode; a positive electrode; a separator; and the electrolyte according to any one of the first to eleventh embodiments.

[0029] Beneficial Effects

[0030] The lithium-sulfur secondary battery electrolyte and the lithium-sulfur secondary battery including the same according to the present disclosure may improve life characteristics by adjusting the solvent, the non-solvent, and the lithium salt contained in the electrolyte to specific conditions. DETAILED DESCRIPTION

[0031] Hereinafter, the present disclosure will be described in more detail.

[0032] It should be understood that the terms or words used in the specification and the appended claims should not be construed as limited to the general meaning and dictionary meaning, but should be interpreted based on the principle of allowing the inventor to appropriately define the terms for the best interpretation, based on the meaning and concepts corresponding to the technical aspects of the present disclosure.

[0033] The term “comprising” or “including” when used in the present specification specifies the presence of stated elements, but does not preclude the presence or addition of one or more other elements, unless the context clearly indicates otherwise.

[0034] Throughout the specification, "A and / or B" means A or B or both A and B.

[0035] In the present disclosure, the “specific surface area” is measured by the Brunauer-Emmett-Teller (BET) method, and specifically, can be calculated from the adsorption amount of nitrogen at liquid nitrogen temperature (77K) using BELSORP-mino II of BEL Japan.

[0036] The term "polysulfide" as used herein covers the concept of "polysulfide ions (S x 2- , x=8, 6, 4, 2)” and “lithium polysulfide (Li 2 S x or LiS x - , x=8,6,4,2)”.

[0037] The term "composite" used herein refers to a material having physically and chemically different phases and more effective functions formed by combining two or more materials.

[0038] The term "porosity" used herein refers to the ratio of the volume of pores to the total volume of a structure, expressed as %, and can be used interchangeably with terms such as pore ratio, void ratio, and the like.

[0039] The present disclosure relates to an electrolyte for a lithium-sulfur secondary battery and a lithium-sulfur secondary battery including the electrolyte.

[0040] The lithium-sulfur secondary battery electrolyte according to one aspect of the present disclosure includes a solvent, a non-solvent, and at least two types of lithium salts, the lithium salt includes LiI, the solvent and the non-solvent have a solvent volume ratio (SVR) factor value of 0.2 to 0.7, and the solvent and the lithium salt have a molar mass ratio (MR) factor value of 0.75 to 1.85.

[0041] Hereinafter, each component will be described in detail.

[0042] The lithium-sulfur secondary battery (a type of secondary battery) is attracting attention as a next-generation secondary battery due to its advantages of high discharge capacity and theoretical energy density, abundant and low-priced sulfur used as a positive electrode active material leading to a reduction in battery manufacturing costs, and eco-friendliness.

[0043] On the other hand, inhibiting the dissolution of polysulfides is one of the challenges of lithium-sulfur secondary batteries, for which slightly solvated electrolyte (SSE) systems have been developed. However, since SSE systems induce solid-phase reactions, it is difficult to maintain the reversible reactions of the positive / negative active materials, and thus short battery life remains an unsolved problem.

[0044] Under such circumstances, the inventors have invented a predetermined electrolyte system, which solves the problems of lithium negative electrode degradation, gas generation in the battery, or inability to maintain the reversible reaction of the positive / negative active materials by using an SSE system and excluding nitric acid and / or nitrous acid electrolyte solvents that are fatal to the life of lithium-sulfur batteries, and using solvents, non-solvents and lithium salts that meet predetermined conditions, thereby improving the life.

[0045] The solvent and the non-solvent have an SVR factor value of 0.2 to 0.7, as shown in Formula 1 below.

[0046] [Formula 1]

[0047] SVR factor = volume of solvent (A) ÷ volume of non-solvent (B)

[0048] In the above Formula 1, the volume of the solvent and the volume of the non-solvent refer to the volumes of the solvent and the non-solvent in the electrolyte, respectively, and the SVR factor value is dimensionless.

[0049] The SVR factor value may be 0.2 to 0.7, and according to an embodiment of the present disclosure, the SVR factor value may be in the range between 0.3 and 0.65 or between 0.4 and 0.5. When the SVR factor value is outside the above range, it is difficult to effectively improve the performance. In particular, when the SVR factor value is greater than 0.7, an excess of lithium polysulfide may be dissolved in the electrolyte, and when the SVR factor value is less than 0.2, the solubility of the lithium salt is too low to produce an electrolyte, or even if an electrolyte is produced, the secondary battery may not function properly due to the low ionic conductivity of the electrolyte.

[0050] In the present disclosure, the solubility of the solvent for the lithium salt may be 0.1 M or more, and the solubility of the non-solvent for the lithium salt may be less than 0.1 M. Specifically, the solubility of the solvent for imide-based lithium salts (such as LiTFSI, LiFSI, LiTF, etc.) may be 0.1 M or more, and the solubility of the non-solvent for the lithium salt may be less than 0.1 M.

[0051] The solvent and the non-solvent may include any types of solvents and non-solvents that are generally used in an electrolyte for a secondary battery and satisfy the solubility conditions and SVR factor values ​​for the lithium salt as described above without limitation.

[0052] In an embodiment of the present disclosure, the solvent may include linear ether, cyclic ether or a mixture thereof.

[0053] For example, the solvent may comprise a linear ether such as dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, diisobutyl ether, ethyl methyl ether, ethyl propyl ether, ethyl tert-butyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, dimethoxypropane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethylene ether, butanediol ether, diethylene glycol ethyl methyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethylene ether, diethylene glycol ethyl methyl ether, diethylene glycol divinyl ether, dipropylene glycol dimethylene ether, diethylene glycol divinyl ether, diethylene glycol divinyl ether, dipropylene ... alkyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol butyl methyl ether, diethylene glycol tert-butyl ethyl ether, ethylene glycol ethyl methyl ether, etc.; cyclic ethers such as dioxolane, methyl dioxolane, dimethyl dioxolane, vinyl dioxolane, methoxy dioxolane, ethyl methyl dioxolane, oxane, dioxane, trioxane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyltetrahydrofuran, dimethoxytetrahydrofuran, ethoxytetrahydrofuran, dihydropyran, tetrahydropyran, furan, 2-methylfuran, etc.; or mixtures thereof.

[0054] On the other hand, the solvent may comprise a mixture of linear ethers and cyclic ethers. Specific examples may include dimethoxyethane and tetrahydrofuran, dimethoxyethane and 2-methyltetrahydrofuran, dimethoxyethane and tetrahydropyran, ethylene glycol diethyl ether and tetrahydrofuran, or ethylene glycol diethyl ether and methyltetrahydrofuran. The mixture containing the linear ether and cyclic ether has a beneficial effect on the stability of the negative electrode and the suppression of gas generation.

[0055] In an embodiment of the present disclosure, the non-solvent may include a fluorinated ether. For example, the non-solvent may include a fluorinated ether compound such as 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE), bis(fluoromethyl) ether, 2-fluoromethyl ether, bis(2,2,2-trifluoroethyl) ether, propyl 1,1,2,2-tetrafluoroethyl ether, isopropyl 1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl isobutyl ether, 1,1,2,3 ,3,3-hexafluoropropyl ethyl ether, 1H,1H,2'H,3H-decafluorodipropyl ether, 1H,1H,2'H-perfluorodipropyl ether, difluoromethyl 2,2,2-trifluoroethyl ether, 1,2,2,2-tetrafluoroethyl trifluoromethyl ether, 1,1,2,3,3,3-hexafluoropropyl difluoromethyl ether, pentafluoroethyl 2,2,2-trifluoroethyl ether, 1H,1H,2'H-perfluorodipropyl ether, etc.

[0056] In the present disclosure, the electrolyte for a lithium-sulfur secondary battery includes at least two types of lithium salts, and the lithium salt includes LiI. That is, the lithium salt may include LiI and at least one type of other lithium salt.

[0057] Other lithium salts may include any compound that provides lithium ions for lithium secondary batteries without limitation. The lithium salt may include imide-based lithium salts, LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCH 3 CO 2 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 , LiCl, LiBr or LiB(C 2 O 4 ) 2 .

[0058] Since imide-based lithium salts are chemically stable and well soluble in organic solvents, when imide-based lithium salts are used as lithium salts of lithium-sulfur secondary batteries, the capacity of lithium-sulfur batteries can be stably maintained and the battery life can be improved. In addition, when two or more imide-based lithium salts are used instead of a single lithium salt, the stability between the lithium negative electrode and the electrolyte can be improved, making it possible to manufacture a secondary battery with a long life.

[0059] For example, the imide-based lithium salt may include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(perfluoroethylsulfonyl)imide (LiBETI), and the like.

[0060] The lithium salt included in the lithium-sulfur secondary battery electrolyte according to an embodiment of the present disclosure may include three different types of lithium salts.

[0061] Specifically, the lithium salt included in the lithium-sulfur secondary battery electrolyte according to an embodiment of the present disclosure may include lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and LiI. When a combination of the above lithium salts is included, side reactions with the negative electrode may be reduced and the reversibility of sulfur may be increased.

[0062] In this case, the content of LiI may be 0.1 to 3.0 parts by weight, or 0.1 to 2 parts by weight based on 100 parts by weight of the lithium-sulfur secondary battery electrolyte. Alternatively, the content of LiI may be 0.35 to 15 parts by weight based on 100 parts by weight of all lithium salts. When the content of LiI is within the above range, the reversibility of sulfur can be increased, thereby improving battery life.

[0063] The molar concentration of all lithium salts may be in the range of 0.1 to 5.0 M, or 0.1 to 3.0 M. Within the above range, the electrolyte may have optimal conductivity and viscosity, and exhibit excellent electrolyte performance, facilitating efficient movement of lithium ions.

[0064] The solvent and the lithium salt have a molar mass ratio (MR) factor value represented by the following Formula 2 of 0.75 to 1.85.

[0065] [Formula 2]

[0066] MR factor = number of moles of solvent ÷ (number of moles of lithium salt excluding LiI).

[0067] In the above formula 2, the mole number of the lithium salt other than LiI refers to the sum of the moles of the lithium salt excluding LiI from all the lithium salts contained in the electrolyte, and the mole number of the solvent refers to the sum of the moles of all the solvents contained in the electrolyte excluding the non-solvent. The MR factor value is dimensionless.

[0068] The MR factor value may be 0.75 to 1.85, and according to an embodiment of the present disclosure, the MR factor value may be in the range of 1.0 to 1.75 or 1.0 to 1.7. When the MR factor value satisfies the above range, the dissolution of lithium polysulfide may be suppressed and the ion conductivity of the electrolyte may be increased, thereby improving the life of the secondary battery.

[0069] For example, a method of calculating the SVR factor value and the MR factor value will be described based on Example 1 described in Table 1 below.

[0070] First, Example 1 contains 2MeTHF (solvent 1): EGDEE (solvent 2): TTE (non-solvent) = 2: 1: 7 (volume ratio), so the SVR factor value is calculated to be (2+1) / 7=0.43.

[0071] Then, Example 1 includes LiTFSI, LiFSI and LiI as lithium salts, but when calculating the MR factor value, LiI is excluded when calculating the moles of all lithium salts. Based on the production of 1 kg of electrolyte, 0.66 mol of 2MeTHF (molar mass: 86.134), 0.73 mol of EGDEE (molar mass: 118.18), 0.71 mol of LiTFSI (molar mass: 287) and 0.23 mol of LiFSI (molar mass 187) are included, so the MR factor value is calculated as (0.66+0.73) / (0.71+0.23)=1.48.

[0072] That is, it was confirmed that Example 1 satisfied the above ranges of the SVR factor value and the MR factor value of the present disclosure, and showed excellent performance in the life evaluation results.

[0073] The electrolyte for a lithium-sulfur secondary battery according to an embodiment of the present disclosure does not include at least one of a nitric acid-based compound and a nitrous acid-based compound.

[0074] Nitric acid and / or nitrous acid compounds are generally used as electrolyte additives to form a stable coating on the lithium electrode and improve the charge and discharge efficiency, but they cannot increase the life due to loss. In this case, the inventors obtained the effect of improving the life without including nitric acid and / or nitrous acid compounds generally used as additives.

[0075] The nitric acid and / or nitrous acid compounds are not limited to specific types in the present disclosure, but may include inorganic nitric acid or inorganic nitrous acid compounds, such as lithium nitrate (LiNO 3 ), potassium nitrate (KNO 3 ), cesium nitrate (CsNO 3 ), barium nitrate (Ba(NO 3 ) 2 ), ammonium nitrate (NH 4 NO 3 ), lithium nitrite (LiNO 2 ), potassium nitrite (KNO 2 ), cesium nitrite (CsNO 2 ), ammonium nitrite (NH 4 NO 2 ) etc.; organic nitric acid or organic nitrite compounds, such as methyl nitrate, dialkyl imidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrite, propyl nitrite, butyl nitrite, amyl nitrite, octyl nitrite, etc.; organic nitro compounds, such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene, etc., or a combination thereof. Specifically, the additive may not contain lithium nitrate (LiNO 3 ).

[0076] On the other hand, the electrolyte may further include other additives to improve charge and discharge characteristics, flame retardancy, etc. Examples of the additives may include pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, fluoroethylene carbonate (FEC), propylene sultone (PRS), vinylene carbonate (VC), etc.

[0077] The method for manufacturing the electrolyte for the lithium-sulfur secondary battery of the present disclosure is not particularly limited, and the electrolyte can be manufactured by any method known in the art.

[0078] In one embodiment of the present disclosure, a lithium-sulfur secondary battery is provided, which includes a negative electrode; a positive electrode; a separator; and the above-mentioned electrolyte.

[0079] The negative electrode includes a negative electrode current collector; and a negative electrode active material layer on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a conductive material, and a binder.

[0080] Specifically, the negative electrode can be manufactured by coating a negative electrode paste on one or two surfaces of a long sheet-shaped negative electrode current collector, drying the negative electrode paste to remove the solvent, and calendering, wherein the negative electrode paste contains the negative electrode active material, the conductive material, and the binder dispersed in the solvent. On the other hand, the negative electrode including an uncoated area can be manufactured by coating the negative electrode paste in such a manner that the negative electrode paste is not coated on a part of the negative electrode current collector (for example, the end of the negative electrode current collector).

[0081] The negative electrode active material can include a material capable of reversibly inserting or extracting lithium ions (Li + ), a material capable of reversibly forming a lithium-containing compound by reacting with lithium ions, lithium metal, or a lithium alloy. The material capable of reversibly inserting or extracting lithium ions can include, for example, crystalline carbon, amorphous carbon, or a mixture thereof, and specifically, can include artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, soft carbon, and hard carbon, but is not limited thereto. The material capable of reversibly forming a lithium-containing compound by reacting with lithium ions can include, for example, tin oxide, titanium nitrate, or a silicon-based compound. The lithium alloy can include, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn). Preferably, the negative electrode active material can be lithium metal, and specifically, can be in the form of a lithium metal foil or lithium metal powder. The silicon-based negative electrode active material can include Si, Si-Me alloy (where Me is at least one selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, and Ni), SiO y (where 0 < y < 2), a Si-C composite, or a combination thereof, and preferably SiO y(where 0 < y < 2). Since the silicon-based negative electrode active material has a high theoretical capacity, the capacity characteristics can be improved when the silicon-based negative electrode active material is included.

[0082] The negative electrode current collector may include a negative electrode current collector commonly used in the related art, and may include, for example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel treated with carbon, nickel, titanium or silver on the surface, and an aluminum-cadmium alloy. The thickness of the negative electrode current collector can generally be 3 μm to 500 μm, and may have fine textures on the surface to enhance the bonding strength of the negative electrode active material. For example, the negative electrode current collector may have various forms, such as a film, sheet, foil, net, porous body, foam, non-woven fabric, etc.

[0083] The conductive material can be used to provide conductive properties to the negative electrode, and may include any conductive material that has the ability to conduct electrons without causing any chemical changes in the corresponding battery without limitation. Specific examples may include graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking carbon black, carbon fiber, carbon nanotube, etc.; metal powders or metal fibers, such as copper, nickel, aluminum, silver, etc.; conductive whiskers, such as zinc oxide, potassium titanate, etc.; conductive metal oxides, such as titanium oxide, etc.; or conductive polymers, such as polyphenylene derivatives, etc.; these conductive materials can be used alone or in combination. Based on the total weight of the negative electrode active material layer, the content of the conductive material can generally be 1 to 30% by weight, 1 to 20% by weight, or 1 to 10% by weight.

[0084] The binder serves to attach the negative electrode active material particles to each other and improve the adhesion strength between the negative electrode active material and the negative electrode current collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof used alone or in combination. Based on the total weight of the negative electrode active material layer, the content of the binder can be 1 to 30% by weight, 1 to 20% by weight, or 1 to 10% by weight.

[0085] The positive electrode includes a positive electrode current collector; and a positive electrode active material layer on at least one surface of the positive electrode current collector, and the positive electrode active material layer contains a positive electrode active material, and may further contain a conductive material, a binder, an additive, etc.

[0086] The positive electrode current collector is configured to support the positive electrode active material, as described in the current collector supporting the negative electrode. For example, the positive electrode current collector may include copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon, copper or stainless steel treated with carbon, nickel or silver on the surface, aluminum-cadmium alloy, etc.

[0087] The positive electrode active material may include sulfur (especially elemental sulfur (S 8 )) and at least one of the group consisting of sulfur compounds. The positive electrode active material may include at least one selected from inorganic sulfur, Li 2 S n (n≥1), disulfide compounds, organic sulfur compounds and carbon-sulfur polymers ((C 2 S x ) n , x=2.5 to 50, n≥2). Specifically, the positive electrode active material may include inorganic sulfur.

[0088] Since sulfur contained in the positive electrode active material itself has no conductivity, sulfur is used in combination with a conductive material (such as a carbon material). Accordingly, sulfur may be contained in the form of a sulfur-carbon composite, and preferably, the positive electrode active material may be a sulfur-carbon composite.

[0089] The carbon included in the sulfur-carbon composite may be a porous carbon material that provides a framework for uniformly and stably fixing sulfur and compensates for low electrical conductivity of sulfur to enhance an electrochemical reaction.

[0090] The porous carbon material can generally be manufactured by carbonization of various carbonaceous precursors. The porous carbon material may contain irregular pores inside. The average diameter of the pores may be in the range of 1 nm to 200 nm, and the porosity may be in the range of 10% to 90% of the total volume of the porous carbon material. When the average diameter of the pores is less than the above range, the pore size is at the molecular level, so that sulfur cannot be loaded. On the contrary, when the average diameter of the pores is greater than the above range, it is not suitable for the electrode manufacturing process due to the low mechanical strength of the porous carbon material.

[0091] The shape of the porous carbon material may be spherical, rod-like, needle-like, plate-like, tubular, or block-like, and may be any shape generally used for lithium-sulfur batteries without limitation.

[0092] The porous carbon material may have a pore structure or a large specific surface area, and includes any porous carbon material commonly used in the art. For example, the porous carbon material may include graphite; graphene; carbon black, such as Dancar black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; carbon nanotubes (CNTs), such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); carbon fibers, such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), activated carbon fibers (ACFs), etc.; graphite, such as natural graphite, artificial graphite, expandable graphite, etc.; activated carbon, etc. Preferably, the porous carbon material may be a carbon nanotube.

[0093] Based on 100 parts by weight of the sulfur-carbon composite, the sulfur-carbon composite may contain 60 to 90 parts by weight, preferably 65 to 85 parts by weight, and more preferably 70 to 80 parts by weight of sulfur. When the sulfur content is less than the aforementioned range, the content of porous carbon material in the sulfur-carbon composite is high, the specific surface area increases, and the binder content increases relative to the sulfur content when the positive electrode is manufactured. The use of a higher content of binder will eventually increase the surface resistance of the positive electrode and hinder the passage of electrons like an insulator, thereby causing the performance of the battery to deteriorate. On the contrary, when the amount of sulfur is greater than the above range, unbound sulfur may form agglomerates or may occur redeposition on the surface of the porous carbon material, which makes it difficult to accept electrons and cannot participate in electrochemical reactions, thereby causing a reduction in battery capacity.

[0094] In addition, in the sulfur-carbon composite, sulfur may be disposed in at least one of the inner surface and the outer surface of the porous carbon material, and in this case, sulfur may be present in an area less than 100%, 1% to 95%, or 60% to 90% of the entire inner and outer surfaces of the porous carbon material. When sulfur is present in the inner and outer surfaces of the porous carbon material within the above range, the maximum effect can be exhibited in terms of electron transfer area and electrolyte wetting. Specifically, since sulfur is thinly and uniformly loaded on the inner and outer surfaces of the porous carbon material in the above range, the electron transfer contact area can be increased during charge and discharge. When sulfur is disposed in an area corresponding to 100% of the entire inner and outer surfaces of the porous carbon material, the carbon material is completely covered with sulfur, resulting in poor electrolyte wetting and little or no contact with the conductive material, thereby being unable to accept electrons at the electrode and participate in the electrochemical reaction.

[0095] The method of manufacturing the sulfur-carbon composite is not particularly limited in the present disclosure and may include any method commonly used in the art. For example, the composite may be formed by simply mixing sulfur with the porous carbon material and heat-treating the mixture.

[0096] In addition to the above components, the positive electrode active material may further include at least one type of additive selected from transition metal elements, Group IIIA elements, Group IVA elements, compounds of these elements with sulfur, and alloys of these elements with sulfur.

[0097] The transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, Hg, etc., the IIIA group elements may include Al, Ga, In, Tl, etc., and the IVA group elements may include Ge, Sn, Pb, etc.

[0098] Based on 100% by weight of the positive electrode active material layer of the positive electrode, the content of sulfur can be 40 to 95% by weight, preferably 50 to 90% by weight, and more preferably 60 to 85% by weight. In one embodiment of the present disclosure, when a sulfur-carbon composite is used as the positive electrode active material, the content of the sulfur-carbon composite can be 90% to 97% by weight based on 100% by weight of the positive electrode active material layer. When the content of the positive electrode active material is less than the aforementioned range, it is difficult to achieve sufficient electrochemical reaction of the positive electrode. On the contrary, when the content of the positive electrode active material is greater than the aforementioned range, the content of the conductive material and the binder as described below is low, the resistance of the positive electrode increases, and the physical properties of the positive electrode decrease.

[0099] Optionally, the positive electrode active material layer may further include a conductive material to allow electrons to smoothly move in the positive electrode (specifically, the positive electrode active material), and a binder to attach the positive electrode active material to a current collector.

[0100] The conductive material is a material that functions as a moving passage for electrons from the current collector to the positive electrode active material by electrically connecting the electrolyte to the positive electrode active material. The conductive material may include any material having conductivity without limitation.

[0101] For example, the conductive material may include graphite, such as natural graphite, artificial graphite, etc.; carbon black, such as Super-P, Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; carbon derivatives, such as carbon nanotubes and fullerenes; conductive fibers, such as carbon fibers and metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; or conductive polymers, such as polyaniline, polythiophene, polyacetylene and polypyrrole, which can be used alone or in combination.

[0102] Based on 100% by weight of the positive electrode active material layer of the positive electrode, the content of the conductive material may be 0.01 to 30% by weight. When the content of the conductive material is less than the aforementioned range, poor electron transfer between the positive electrode active material and the current collector is caused, thereby causing a decrease in voltage and capacity. On the contrary, when the content of the conductive material is greater than the aforementioned range, the proportion of the positive electrode active material is low, and the total energy (charge) of the battery is reduced. Therefore, it is preferred to determine the optimal amount of the conductive material within the aforementioned range.

[0103] The binder plays a role of binding the positive electrode active material to the positive electrode current collector and connecting the positive electrode active materials to each other to increase bonding strength, and may include any known binder.

[0104] For example, the adhesive includes a fluororesin-based adhesive, including polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE); a rubber-based adhesive, including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber and styrene-isoprene rubber; a cellulose-based adhesive, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose and regenerated cellulose; a polyol-based adhesive; a polyolefin-based adhesive, including polyethylene and polypropylene; a polyimide-based adhesive; a polyester-based adhesive; and a silane-based adhesive, or a mixture thereof or a copolymer thereof.

[0105] Based on 100 wt % of the positive electrode active material layer of the positive electrode, the content of the binder may be 0.5 to 30 wt %. When the content of the binder is less than 0.5 wt %, the performance of the positive electrode may be reduced, and the positive electrode active material and the conductive material may be peeled off. When the content of the binder is greater than the above range, the ratio of the positive electrode active material and the conductive material in the positive electrode is reduced, and the capacity of the battery may be reduced. Therefore, it is preferred to determine the optimal content of the binder within the above range.

[0106] The separator can separate the negative electrode from the positive electrode and provide a mobile channel for lithium ions, and can include any type of separator commonly used in lithium secondary batteries without limitation. Specifically, the separator can include a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer (such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer) or a stacked structure of more than two layers thereof. In addition, commonly used porous nonwoven fabrics can be used, for example, nonwoven fabrics made of high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, a coated separator comprising ceramic or polymer materials can be used to ensure heat resistance or mechanical strength.

[0107] The lithium-sulfur battery is not limited to a specific shape and may have various shapes such as a cylindrical shape, a stacked type, a coin type, and the like.

[0108] In addition, the present disclosure provides a battery module including the lithium-sulfur battery as a unit cell. The battery module can be used as a power source for medium and large-sized devices requiring high temperature stability, long cycle characteristics, and high capacity characteristics.

[0109] Examples of the medium and large devices may include devices that work using electricity generated by electric motors, such as power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles, including electric bicycles and electric scooters; electric golf carts; and energy storage systems, but are not limited to these.

[0110] Hereinafter, the present disclosure will be described in detail by embodiments / examples. However, embodiments / examples according to the present disclosure may be modified in many other forms, and the scope of the present disclosure should not be interpreted as being limited to the embodiments / examples described below. Embodiments / examples of the present disclosure are provided to thoroughly and completely describe the present disclosure to those skilled in the art.

[0111] Examples 1 to 12 and Comparative Examples 1 to 5

[0112] Preparation of electrolyte

[0113] An electrolyte including a solvent, a non-solvent, and a lithium salt was prepared to satisfy the SVR factor value, MR factor value, and the amount of LiI specified in Table 1 below.

[0114] In this case, 2-methyltetrahydrofuran (2MeTHF), ethylene glycol diethyl ether (EGDEE), tetrahydrofuran (THF), tetrahydropyran (THP), dimethyl ether (DME) or a mixture thereof is used as a solvent, 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE) is used as a non-solvent, and lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and LiI are used as lithium salts.

[0115] Cathode Manufacturing

[0116] 90 parts by weight of a sulfur-carbon composite (S:C=75:25 weight ratio) as a positive electrode active material (based on the total weight of the positive electrode, the amount of sulfur alone is set to 67.5 weight %, and the carbon composite having a thickness of 1.8 cm 3 / g pore volume of activated carbon as a carbon material), 5 parts by weight of Danka black as a conductive material and 5 parts by weight of styrene butadiene rubber / carboxymethyl cellulose (SBR:CMC=7:3 (weight ratio)) as a binder were mixed to prepare a positive electrode slurry composition, and the slurry composition was coated on a current collector (Al foil), dried at 50°C for 12 hours and pressed using a roller press to manufacture a positive electrode (in this case, the loading amount was 3.5 mAh / cm 2 , and the porosity of the electrode is 65%).

[0117] Lithium-sulfur battery manufacturing

[0118] The positive electrode prepared as above and a 150 μm thick lithium metal negative electrode were placed with a polyethylene (PE) separator interposed therebetween, and the prepared electrolyte was injected to manufacture a coin cell type lithium-sulfur battery. On the other hand, in the manufacture of the battery, the positive electrode was punched into a 14 phi circular electrode, the polyethylene separator was punched to 19 phi, and the lithium metal was punched to 16 phi. In addition, the battery was manufactured using a slightly solvated electrolyte (SSE) electrolyte system.

[0119]

[0120] Lifespan evaluation

[0121] In order to determine the life characteristics of the lithium-sulfur secondary batteries prepared in the embodiments and comparative examples, discharge and charge were repeated 2.5 times at a current density of 0.1 C, and then charged at a current density of 0.2 C and discharged at a current density of 0.5 C for 150 cycles, and at the same time, the life cycle when the capacity retention rate of the lithium-sulfur secondary battery was 80% was measured.

Claims

1. An electrolyte for a lithium-sulfur secondary battery, comprising: a solvent, a non-solvent and at least two lithium salts, wherein the lithium salt comprises LiI, wherein the solvent and the non-solvent have a solvent volume ratio (SVR) factor value of 0.2 to 0.7, and the SVR factor value is represented by the following formula 1, and wherein the solvent and the lithium salt have a molar mass ratio (MR) factor value of 0.75 to 1.85, and the MR factor value is represented by the following Formula 2, [Formula 1] SVR factor = volume of solvent ÷ volume of non-solvent [Formula 2] MR factor = number of moles of solvent ÷ (number of moles of lithium salt excluding LiI). 2 . The electrolyte for a lithium-sulfur secondary battery according to claim 1 , wherein the SVR factor value is 0.3 to 0.

65. 3 . The electrolyte for a lithium-sulfur secondary battery according to claim 1 , wherein the MR factor value is 1.0 to 1.

75.

4. The electrolyte for a lithium-sulfur secondary battery according to claim 1, wherein the solvent has a solubility of 0.1 M or more for the lithium salt, and The non-solvent has a solubility of less than 0.1M for the lithium salt. 5 . The electrolyte for a lithium-sulfur secondary battery according to claim 4 , wherein the solvent comprises a linear ether, a cyclic ether or a mixture thereof. 6 . The electrolyte for a lithium-sulfur secondary battery according to claim 4 , wherein the solvent comprises a mixture of a linear ether and a cyclic ether. 7 . The electrolyte for a lithium-sulfur secondary battery according to claim 4 , wherein the non-solvent comprises a fluorinated ether. 8 . The electrolyte for a lithium-sulfur secondary battery according to claim 1 , wherein the lithium salt comprises lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and LiI. 9 . The electrolyte for a lithium-sulfur secondary battery according to claim 1 , wherein the content of the LiI is 0.1 to 3.0 parts by weight based on a total of 100 parts by weight of the electrolyte for a lithium-sulfur secondary battery. 10 . The electrolyte for a lithium-sulfur secondary battery according to claim 8 , wherein the content of the LiI is 0.35 to 15 parts by weight based on a total of 100 parts by weight of the lithium salt. 11 . The lithium-sulfur secondary battery electrolyte according to claim 1 , wherein the lithium-sulfur secondary battery electrolyte does not contain at least one of a nitric acid compound and a nitrous acid compound.

12. A lithium-sulfur secondary battery comprising: A negative electrode; a positive electrode; a separator; and an electrolyte according to any one of claims 1 to 11.